1984
DOI: 10.1017/s0022172400060861
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a nonplasmid-located determinant for gentamicin resistance in strains ofStaphylococcus aureus

Abstract: SUMMARYThe occurrence of resistance to gentamicin in strains of Staphylococcus aureu-s with different phage patterns in two hospitals is described. The data suggest transfer of gentamicin resistance between different strains. In the strains investigated the determinant for resistance to gentamicin (parallel resistance to kanamycin and tobramycin) is located on the chromosome. The transfer of this resistance determinant in a mixed culture of donor and recipient cells in vitro is mediated by transduction because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…During the late 1970s and early 1980s, strains of S. aureus resistant to multiple antibiotics including methicillin and gentamicin were increasingly responsible for outbreaks of hospital infections in countries around the world, e.g., Argentina (440), Austria (472), Australia (152,234,376,377,508), Belgium (558), Denmark (133,414), Republic of Ireland (63,64,192), England (44,393,449), France (125,166), East and West Germany (339,549), Greece (151), Italy (525), Japan (242), and the United States (94, 184,437,538). In many instances, these outbreaks were associated with indi-vidual wards or units, with neonatal (152,183,393), intensive care (498), and burns units (17,42) being particularly susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…During the late 1970s and early 1980s, strains of S. aureus resistant to multiple antibiotics including methicillin and gentamicin were increasingly responsible for outbreaks of hospital infections in countries around the world, e.g., Argentina (440), Austria (472), Australia (152,234,376,377,508), Belgium (558), Denmark (133,414), Republic of Ireland (63,64,192), England (44,393,449), France (125,166), East and West Germany (339,549), Greece (151), Italy (525), Japan (242), and the United States (94, 184,437,538). In many instances, these outbreaks were associated with indi-vidual wards or units, with neonatal (152,183,393), intensive care (498), and burns units (17,42) being particularly susceptible.…”
Section: Introductionmentioning
confidence: 99%
“…Also, naturally occurring strains possess such translocatable elements integrated into their chromosomes (Iilactamase in strain PS80 [1]; macrolide, lincosamide, and streptogramin B resistance in discrete multiple-antibioticresistant hospital strains [27]; aminoglycoside resistance in different multiple-antibiotic-resistant strains [28]). From previous studies of different penicillinase plasmids of S. aureus (22), it was concluded that the mercury resistance determinants on the 6.3-kb BglII fragment might be a part of a translocatable element which became integrated into different plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…The agar diffusion test with disks loaded with mercuric chloride and phenylmercury acetate was described previously (25). Growth inhibition by Cd2+ c Determined as described previously (12,28,29). RTD, Routine test dilution; NT, not typable at 100 times the routine test dilution.…”
mentioning
confidence: 99%
“…In recent years, Pcf in S. aureus isolates from the USA and Europe has been attributed either to P-lactamaselheavy metal resistance plasmids or to the presence of a family of selftransmissible plasmids which also encode resistance to the aminoglycosides gentamicin (Gm), tobramycin (Tm) and kanamycin (Km) and to quaternary ammonium compounds (Qa) and ethidium bromide (Eb) (Goering & Ruff, 1983;Witte & Dunnhaupt, 1984). The Pcr region of one of these plasmids, pCRG1600, was shown to lie within a 6.7 kb transposon, designated Tn4201, which is capable of undergoing rec-independent translocation between plasmids and the chromosome (Weber & Goering, 1988).…”
Section: Introductionmentioning
confidence: 99%